Neutralizing Potency of Prototype and Omicron RBD mRNA Vaccines Against Omicron Variant - Zang, Jinkai; Yin, Yannan; Xu, Shiqi; Qiao, Weihua; Liu, Qiuyue; Lavillette, Dimitri; Zhang, Chao; Wang, Haikun; Huang, Zhong (Frontiers in Immunology, 2022)
The newly emerged Omicron variant of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) contains more than 30 mutations on the spike protein, 15 of which are located within the receptor binding domain (RBD). Consequently, Omicron is able to extensively escape existing neutralizing antibodies and may therefore compromise the efficacy of current vaccines based on the original strain, highlighting the importance and urgency of developing effective vaccines against Omicron. Here we report the rapid generation and evaluation of an mRNA vaccine candidate specific to Omicron, and explore the feasibility of heterologous immunization with WT and Omicron RBD vaccines. This mRNA vaccine encodes the RBD of Omicron (designated as RBD-O) and is formulated with lipid nanoparticle. Two doses of the RBD-O mRNA vaccine efficiently induce neutralizing antibodies in mice; however, the antisera are effective only on the Omicron variant but not on the wildtype and Delta strains, indicating a narrow neutralization spectrum. It is noted that the neutralization profile of the RBD-O mRNA vaccine is opposite to that observed for the mRNA vaccine expressing the wildtype RBD (RBD-WT). Importantly, booster with RBD-O mRNA vaccine after two doses of RBD-WT mRNA vaccine can significantly increase neutralization titers against Omicron. Additionally, an obvious increase in IFN-γ, IL-2, and TNF-α-expressing RBD-specific CD4+ T cell responses was observed after immunization with the RBD-WT and/or RBD-O mRNA vaccine. Together, our work demonstrates the feasibility and potency of an RBD-based mRNA vaccine specific to Omicron, providing important information for further development of heterologous immunization program or bivalent/multivalent SARS-CoV-2 vaccines with broad-spectrum efficacy.